Combustion instability and ash agglomeration in wood pellets boiler - Fraga, Lelis (2023)
The combustion instability and ash agglomeration in a wood pellet boiler were investigated in this study. The tests were conducted using the Taguchi method of orthogonal array L27(133). Several parameters are applied, including grate area (GA), primary to secondary air split ratio (SR), excess air (EA), and fuel power (P). Pine wood pellets were used, and the boiler’s nominal load was 20 kW. The results show that instability during combustion occurs since the fuel bed rises as the accumulation of the unburned wood pellets on the grate causes a slow combustion rate and pressure drop, which creates noise and disturbances. A good combination of the parameters applied to TN9 and TN20 can be useful in obtaining stable combustion. In addition, the ash agglomerations were influenced by the duration of the combustion and the temperature of the fuel bed. The largest size of the ash agglomeration was referred to as test number-TN26 (P: 16 kW, EA: 110%, SR: 30/70, and GA: 115 mm × 75 mm), which is 59 mm, and the duration time is 14,400 s (≈4 h).